PEMANFAATAN BATANG PISANG (MUSA PARADISIACA L) DALAM PEMBUATAN PULP DENGAN MENGGUNAKAN METODE ACETOSOLV SERTA IMPLEMENTASINYA DI SEKOLAH - zona Octarya (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
AbstractAcetosolv process is one of making pulp alternative which friendly environmental. Making pulp of banana stem with a solution of acetic acid cooking (CH3COOH) and catalyst sulfate acid (H2SO4) are expected to take place simultaneously, either delignification process or degradation of polisakarida. The variable process is looked in this research is concentration of acetic acid (70%-wt, 80%-wt, 90-wt%) with cooking time (1 hour, 2 hours, 3 hours), whereas constant variabel in this research in liquid to solid ratio (20/1), concentration catalyst (0.6%-wt), and measure of raw materials (±1,5cm). The result of the study exhibit banana stem may become as raw material in making pulp which using acetosolv. Yield pulp around 50.64 % -57.13% with content of lignin pulp 12.5% -19.42%, and content of cellulose pulp 80,85%-82,28%, which is variation according to process. The best condition which produce yield with high cellulose level and low lignin are gotten at concentration of cooking 90%-wt with time of cooking 3 hours. The result shows that banana stem pulp have yield of 50.64%, lignin 12.5% and cellulose 87.49%. Implementation knowledge of student senior high school 1 Tembilahan to exploiting banana stem in making pulp categorized as "very good" because the final results show the percentage obtained 86.78% which lies in the range of 81% -100%, this percentage is in the category of "very good ''. Keywords:  Banana stem, Acetosolv, Yield pulp, Lignin, Cellulose, Implementation.